2006
DOI: 10.1091/mbc.e05-11-1008
|View full text |Cite
|
Sign up to set email alerts
|

Postreplication Repair and PCNA Modification inSchizosaccharomyces pombe

Abstract: Ubiquitination of proliferating cell nuclear antigen (PCNA) plays a crucial role in regulating replication past DNA damage in eukaryotes, but the detailed mechanisms appear to vary in different organisms. We have examined the modification of PCNA in Schizosaccharomyces pombe. We find that, in response to UV irradiation, PCNA is mono-and poly-ubiquitinated in a manner similar to that in Saccharomyces cerevisiae. However in undamaged Schizosaccharomyces pombe cells, PCNA is ubiquitinated in S phase, whereas in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
178
1
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(202 citation statements)
references
References 40 publications
(54 reference statements)
15
178
1
8
Order By: Relevance
“…We note that the pcn1-K164R mutation confers greater MMS sensitivity than does the 3TLSD strain and that pcn1-K164R cells are sensitive to UV-C irradiation in G 2 , whereas 3TLSD cells are not (Frampton et al 2006). We also note that the requirement for Rhp18 extends to the repair of lesions in cells irradiated in G 2 (Verkade et al 2001).…”
Section: Brc1 Suppresses Smc6-74 Via a Novel Prr Pathwaymentioning
confidence: 65%
See 1 more Smart Citation
“…We note that the pcn1-K164R mutation confers greater MMS sensitivity than does the 3TLSD strain and that pcn1-K164R cells are sensitive to UV-C irradiation in G 2 , whereas 3TLSD cells are not (Frampton et al 2006). We also note that the requirement for Rhp18 extends to the repair of lesions in cells irradiated in G 2 (Verkade et al 2001).…”
Section: Brc1 Suppresses Smc6-74 Via a Novel Prr Pathwaymentioning
confidence: 65%
“…Analysis of PCNA ubiquitination: Ubiqutination of PCNA was detected by Western blotting using polyclonal anti-PCNA antisera as described (Frampton et al 2006). Note that this antiserum detects a nonspecific band that comigrates with diubiquitinated PCNA.…”
mentioning
confidence: 99%
“…18 However, in contrast to budding yeast, damage-induced ubiquitylation can occur outside of S phase even in untransfected cells. 19 In S. pombe, PCNA mono-ubiquitylation occurs constitutively in S phase, 20 resembling conditions of RAD18 overexpression in S. cerevisiae. Thus, variations in the requirements for PCNA ubiquitylation among different organisms may reflect differences in the expression levels of RAD18.…”
Section: Rad18 Is a Limiting Factor For Pcna Ubiquitylation At Stallementioning
confidence: 98%
“…59 In eukaryotes it has recently been discovered that posttranslational modification of the PCNA processivity clamp by ubiquitination is required for TLS in vivo. [60][61][62][63] Furthermore, interaction with PCNA is a requirement for focus formation of pol k in response to DNA damage. 64 The alternative processivity clamp Rad9-Rad1-Hus1 (9-1-1) has been also shown to be important for DinB function in Schizosaccharomyces pombe.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…Moreover, whether selection of the proper polymerase occurs merely by stochastic competition or by more a more orchestrated mechanism is a topic of intense debate. 62,66,68,69 Another key question is whether TLS occurs solely at static stalled replication forks or perhaps additionally at gaps left after replication reinitiation. Recent results in S. cerevisiae have suggested that replication blocking lesions can induce both leading and lagging strand gaps, 70 evoking early models of replication in E. coli.…”
Section: Conclusion and Future Questionsmentioning
confidence: 99%